Guidelines for drinking-water quality. Vol. 1, Recommendations (WHO, 2006)
The First Addendum to Volume 1 of the Third Edition of the Guidelines for Drinking-water Quality provides a detailed list of all changes to the Guidelines that have occurred since the Third Edition was published in 2004. It adds three new chemical fact sheets (1,4-Dioxane, MTBE, Petroleum oils) and revises several others(Formaldehyde, Mercury, Nickel, Trichloroethene, THMs, Permethrin, Chlorite and Chlorate. It updates the guideline summary tables; provides new text to address local actions in response to chemical water quality problems and emergencies; expands the discussion of chemicals used in water treatment and chemicals arising from materials in contact with water; and provides a complete list of minor revisions of or amendments to the text of the Third Edition.
Keywords: řízení kvality; Aquaculture; Water Supply; Quality Control; Water Microbiology; mikrobiologie vody; zásobování vodou; vodní hospodářství; hygiena